Long-term durability and ecotoxicity of biocomposites in marine environments: a review. Issue 52 (7th October 2021) - Curto, Marco; Le Gall, Maelenn; Catarino, Ana Isabel; Niu, Zhiyue; Davies, Peter; Everaert, Gert; Dhakal, Hom N.
Abstract : Long term durability and moisture ingress effects on the mechanical property is highlighted where tensile strength is reduced as the moisture immersion time increases showing weak fibre matrix interfaces evidenced from SEM micrograph. Abstract : There is a growing interest in replacing fossil-based polymers and composites with more sustainable and renewable fully biobased composite materials in automotive, aerospace and marine applications. There is an effort to develop components with a reduced carbon footprint and environmental impact, and materials based on biocomposites could provide such solutions. Structural components can be subjected to different marine conditions, therefore assessment of their long-term durability according to their marine applications is necessary, highlighting related degradation mechanisms. Through an up-to-date review, this work critically discusses relevant literature on the long-term durability of biocomposites specific for marine environments. Importantly, in this review we report the effects of abiotic parameters, such as the influence of hygrothermal exposures (temperatures and UV radiation) on physical, mechanical and thermal characteristics of biocomposites. Furthermore, we identify and discuss the potential ecotoxicological effects of leaching substances and microplastics derived from biocomposites, as well as the change in mechanical, physical and thermal behaviours correlated to degradation in the fibre matrix interface, surface defects and overall deterioration of the composite's properties. Finally, the combined effects of various environmental exposures on the long-term durability of the biocomposites are critically reviewed.